2016
DOI: 10.18632/oncotarget.7008
|View full text |Cite
|
Sign up to set email alerts
|

Does bevacizumab impact anti-EGFR therapy efficacy in metastatic colorectal cancer?

Abstract: Anti-EGFR therapy and antiangiogenic therapies are used alone or in combination with chemotherapies to improve survival in metastatic colorectal cancer. However, it is unknown whether pretreatment with antiangiogenic therapy could impact on the efficacy of anti-EGFR therapy.We selected one hundred and twenty eight patients diagnosed with advanced colorectal cancer with a KRAS and NRAS unmutated tumor. These patients were treated with cetuximab or panitumumab alone or with chemotherapy as second or third-line. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 31 publications
6
36
0
3
Order By: Relevance
“…Similar to our study, the Prodige 18 study and several retrospective studies have also demonstrated that prior bevacizumab therapy decreases the efficacy of subsequent cetuximab therapy. Although Modest et al reported that the application of anti‐EGFR therapy as first‐line therapy may represent a favorable condition for promoting the effectiveness of subsequent antiangiogenic agents, the diversity of second‐line therapy and imbalance of later‐line regimens contributed to the uncertainness of this result.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar to our study, the Prodige 18 study and several retrospective studies have also demonstrated that prior bevacizumab therapy decreases the efficacy of subsequent cetuximab therapy. Although Modest et al reported that the application of anti‐EGFR therapy as first‐line therapy may represent a favorable condition for promoting the effectiveness of subsequent antiangiogenic agents, the diversity of second‐line therapy and imbalance of later‐line regimens contributed to the uncertainness of this result.…”
Section: Discussionsupporting
confidence: 90%
“…Preclinical studies in animal models and cancer cell lines have shown that after resistance to EGFR inhibitors was developed, constitutively high expression of VEGF, vascular endothelial growth factor receptor‐1(VEGFR‐1), and placental growth factor (PlGF) were noted, and inhibition of the VEGF pathway by VEGF inhibitor treatment was shown to be effective . In contrast, after bevacizumab pretreatment, hypoxia was induced in cancer cell lines, and subsequent EGFR‐independent RAS activation rendered the cells less sensitive to subsequent EGFR blockade . These phenomena might explain this study results; bevacizumab as third‐line therapy leads to prolonged duration of SD because this therapy alters the tumor microenvironment through the inhibition of VEGF/VEGFR.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Unter der Behandlung mit Bevacizumab plus Chemotherapie traten im Vergleich zur alleinigen Behandlung mit Chemotherapie folgende Grad-3 -5-Ereignisse häufiger auf: Blutungen/Hämorrhagie (2 vs. < 1 %), gastrointestinale Perforationen (2 vs. < 1 %) und venöse thromboembolische Ereignisse (5 vs. 3 %). Retrospektive klinische Untersuchungen weisen darauf hin, dass eine anti-EGFR-Therapie dann weniger wirksam ist, wenn ihr eine anti-VEGF-Therapie voranging [1168]. Präklinische Daten stützen diese Hypothese [1169,1170].…”
Section: Fortführung Der Anti-vegf-therapie In Der Zweitlinienbehandlungunclassified